European Union’s carbon border adjustment mechanism addressing carbon leakage : Influence on Finnish foreign trade - Laakso, Olga (My University, 2025)
The European Union (EU) aims to become the first carbon-neutral continent by 2050. To achieve this, the union has adopted ambitious climate legislation, which includes the first large-scale emissions trading system in action in the world. However, different levels of climate ambition across countries pose a risk of carbon leakage. To address carbon leakage, the EU is setting up a carbon border adjustment mechanism (CBAM). This will be the first of its kind globally. Its influence on small and export-dependent member states such as Finland calls for a closer examination, particularly in terms of competitiveness. The aim of this study is to explore how does the implementation of the EU's CBAM influence Finnish foreign trade. This question is approached by first establishing a theoretical framework on the role of trade policy in climate change mitigation, carbon leakage and the academic debate on the mechanism. A qualitative approach is adopted, as it allows EU CBAM to be examined within its complex and trade policy context. The empirical data for the study is collected through expert interviews, which are complemented by secondary data. The collected data is analysed using thematic analysis. This makes it possible to see the influence of the mechanism on Finland's foreign trade in the light of most recent knowledge on the mechanism. The results suggest that the implementation of the carbon border mechanism may have unexpected effects on the competitive position of Finnish companies, which may have negative implications for Finland's exports. This is related to increasing reporting requirements for companies, differences in the level of implementation between Member States and differences in state aid policy. In addition, the trade policy reactions of the EU's trading partners to the mechanism could pose a risk to Finland's foreign trade. The Commission's new Omnibus initiative aimed at simplifying regulation would, if implemented, address some of the problems identified. If it is decided to extend EU CBAM from its current scope, it is important to ensure a gradual transition based on comprehensive impact assessments to which all member states can commit.

Euroopan unionin (EU) tavoitteena on olla ensimmäinen hiilineutraali maanosa vuoteen 2050 mennessä. Tavoitteen saavuttamiseksi EU on ottanut käyttöön ilmastotavoitteiden kannalta kunnianhimoista lainsäädäntöä, kuten ensimmäinen laajamittainen päästökauppajärjestelmän. Riskinä eri valtioiden ilmastopolitiikan kunnianhimon tasojen erotessa toisistaan kuitenkin on olemassa hiilivuoto EU:sta. Ehkäistäkseen hiilivuotoa tehokkaammin EU on ottamassa käyttöön hiilirajamekanismin ensimmäisenä maailmassa. Sen vaikutusta Suomen kaltaisiin pieniin viennistä riippuvaisiin jäsenvaltioihin on syytä tarkastella tarkemmin erityisesti kilpailukyvyn kannalta. Tämän pro gradu -tutkielman tavoitteena on selvittää, miten Euroopan unionin hiilirajamekanismi tulee vaikuttamaan Suomen ulkomaankauppaan. Tätä kysymystä lähestytään muodostamalla ensin teoreettinen viitekehys kauppapolitiikan roolista ilmastonmuutoksen ehkäisemisessä, hiilivuodosta ja itse mekanismista. Tutkimus toteutetaan laadullisena, sillä se mahdollistaa hiilirajamekanismin tutkimisen osana sen monitahoista ja kaupallispoliittista kontekstia. Tutkimuksen empiirinen aineisto kerätään asiantuntijahaastatteluissa, jota täydennetään sekundääriaineistolla. Kerätty aineisto analysoidaan temaattisen analyysin keinoin. Näin on mahdollista tarkastella, mekanismin vaikutuksia Suomen ulkomaankauppaan tuoreimman mekanismia koskevan tiedon valossa. Tulosten mukaan hiilirajamekanismin käyttöönotolla voi olla odottamattomia vaikutuksia suomalaisten yritysten kilpailuasetelmiin, mikä voi negatiivisesti heijastua Suomen vientiin. Tämän taustalla on yritysten kasvavat raportointivelvoitteet, erot toteutuksen tasossa jäsenvaltioiden välillä ja erot valtiontukipolitiikassa. Lisäksi riskinä Suomen ulkomaankaupalle on EU:n kauppakumppaneiden kauppapoliittiset reaktiot mekanismiin. Komission uusi sääntelyn yksinkertaistamiseen tähtäävä Omnibus-aloite vastaisi toteutuessaan osaan havaituista ongelmista. Mikäli hiilirajamekanismia päädytään laajentamaan, on tärkeää varmistaa asteittainen ja kattaviin vaikutusarviointeihin perustuva siirtymä, johon kaikki jäsenvaltiot pystyvät sitoutumaan.
Keywords: CBAM, European Union, carbon leakage, Finnish foreign trade, hiilirajamekanismi, Euroopan unioni, hiilivuoto, Suomen ulkomaankauppa